The ultrasonic welding operations technological regimes impact on the process connections reliability - Пономарева, А.В.; Невлюдова, В.В. (Radiotekhnika, 2012)
The constructing process of ultrasonic microwelding technological operation mathematical model and optimization of its parameters using the methods of the factor analysis are elucidated. The obtained model will make it possible to improve the quality of the welded microbonds and to decrease the faults level.